Fabrication of Aligners Using Digital Technologies in Orthodontics - Anvar, Rustamov Elshan; Rasim, Mehmani Vusala; Sergey, Ashrafov Davud (American Journal of Biology and Natural Sciences, 2025)
Modern orthodontics has developed a comfortable and effective method for correcting malocclusion using aligners, which are completely invisible on the teeth and cause no discomfort to the patient. Aligners are made from a special type of thermoplastic material. During use, they exert a gentle yet continuous pressure on the teeth, gradually moving them along a predetermined trajectory toward the desired position. Over the past decade, removable orthodontic thermoplastic appliances — aligners — have become a popular alternative to conventional fixed systems and orthodontic devices designed to correct malocclusion by applying forces that induce controlled tooth movement. The technology for designing and fabricating aligners makes it possible to develop an individual alignment system with full control over thickness, coverage, and attachment elements.